Development and characterization of collagen type I and hyaluronic acid (HA) based interlaced scaffolds for tissue engineered heart valves (TEHVS) - Nazir, R (2017)
An ideal scaffold for the regeneration of valvular tissue should replicate the natural heart valve extracellular matrix (ECM) in terms of microstructure and properties. Tissue engineers have achieved limited success so far in designing an ideal scaffold; scaffolds lack in mechanical compatibility, appropriate degradation rate, and microstructural similarity. This thesis, therefore, is the first attempt to develop interlaced scaffolds from collagen type I and hyaluronic acid (HA), polymers found in the natural valve, via a modified carbodiimide based crosslinking technique. Scanning electron micrographs (SEM) and images of Alcian blue – Periodic acid Schiff (PAS) stained samples suggested that our crosslinking technique yielded an ECM mimicking microstructure with interlaced bands of collagen and HA in the hybrid scaffolds. Hybrid scaffolds also offered a wide range of pore size (66 – 126 μm) which fulfilled the criteria for valvular tissue regeneration. Swelling studies revealed that crosslinking densities of parent networks increased with increasing the concentration of the crosslinking agents whereas crosslinking densities of hybrid scaffolds averaged from those of parent collagen and HA networks. Fourier transform infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA) showed that this technique could crosslink collagen type I and HA without denaturation. Also, no intermediate phase formation between collagen and HA could be detected. Elastic moduli increased with increasing crosslinking densities, in the dry and wet state, for parent networks whereas those of interlaced scaffolds were higher than either network alone. Compressive, bending, and storage moduli ranged from 35 ± 5 kPa to 95 ± 5 kPa, 154 ± 12 kPa to 1660 ± 7 kPa, and 16 ± 2 kPa to 113 ± 6 kPa respectively in the dry state. Corresponding wet mechanical moduli ranged from 1 ± 0.3 kPa to 5 ± 0.1 kPa, 7 ± 2 kPa to 55 ± 4 kPa, and 2 ± 0.4 to 9 ± 2 respectively. Bending and storage moduli, in the dry state, matched and exceeded those of human aortic valve leaflets (HAVL). Similarly, degradation resistance increased with increasing the crosslinking densities for collagen only and HA only scaffolds. Interlaced scaffolds showed partial degradation in the presence of either collagenase or hyaluronidase as compared to when exposed to both enzymes together. These results agreed with FTIR and SEM that interlaced scaffolds were composed of independent collagen and HA networks without crosslinking between them. Cardiosphere derived cells (CDCs) attached and proliferated on all scaffolds in cell culture experiments as confirmed by AlamarBlue® assay and SEM images. The increase in crosslinking density, however, affected the cell affinity because of the engagement of the cell-attachment sites in the crosslinking process. CDCs seeded scaffolds also showed 50 % increase in bending modulus after 28 days of culture. While evaluated against the criterion for tissue engineered heart valve (TEHV), S-3 and S-4 among interlaced scaffolds/compositions not only matched mechanically but also showed high degradation resistance which potentially made them as 'close-fit' candidates. Findings from this thesis indicated that collagen/HA interlaced scaffolds have the potential to fill in the niche for designing an ideal TEHV. Furthermore, the properties of the interlaced scaffolds, fabricated by our crosslinking technique, can be tailored by controlling the crosslinking density which can also widen the scope of these scaffolds for other tissue engineering applications such as bone, cartilage etc.